Experimental Study of the Use of Rubber Seeds as Biodiesel Feedstocks; Production Optimization, Characterization and Performance Testing - Tambunan, Bisrul Hapis (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2024)
This study's objective was to create and characterize biodiesel from rubber seeds. Rubber seeds collected from smallholder plantations in the northern Sumatra region of Indonesia are peeled to separate the shell from the kernel. The rubber seed kernels are boiled for 4 hours to boiled to release the sap. The boiled kernels are drained and dried in the sun for two days in sunny weather. Furthermore kernels boiled and dried are pressed with a screw press machine, and RSO (rubber seed oil) is obtained. This RSO is produced into RSB (Rubber Seed Biodiesel) using a double jacket reactor through degumming, esterification, and trans-esterification stages. Biodiesel production is carried out with variations in the ratio of catalysts, temperature, and reaction time. For each of these variables, the yield of biodiesel produced is calculated. Then the biodiesel produced was characterized through psycho-chemical property testing, including calorific value, cetane number, oxidation stability, density, viscosity, acid content, pour point, and flash point. Furthermore, the biodiesel was tested on a diesel engine at several engine speeds to observe its performance and emissions. In biodiesel production, the maximum yield is the catalyst/crude oil ratio = 0.75, the oil/methanol molar ratio = 1:1.25, the reaction temperature is 60 oC and the reaction time is 100 minutes, but the yield increase from 90 minutes to 100 minutes is not significant. RSB meets ASTM biodiesel standards except for oxidation stability, which is 1.2 hours instead of 3 hours. RSB engine performance and exhaust emissions are comparable to biodiesel in general.